Thermal performance of tubular heat exchanger with multiple twisted-tape inserts - Chokphoemphun, Suriya; Pimsarn, Monsak; Thianpong, Chinaruk; Promvonge, Pongjet (My University, 2015)
The paper presents an experimental investigation on enhanced heat transfer and pressure loss characteristics by using single, double, triple, and quadruple twisted-tape inserts in a round tube having a uniform heat-fluxed wall. The investigation has been conducted in the heat exchanger tube inserted with various twisted-tape numbers for co- and counter-twist arrangements for the turbulent air flow, Reynolds number (Re) from 5300 to 24000. The typical single twisted-tape inserts at two twist ratios, y/w = 4 and 5, are used as the base case, while the other multiple twisted-tape inserts are at y/w = 4 only. The experimental results of heat transfer and pressure drop in terms of Nusselt number (Nu) and friction factor (f), respectively, reveal that Nu increases with the increment of Re and of twisted-tape number. The values of Nu for the inserted tube are in a range of 1.15-2.12 times that for the plain tube while f is 1.9-4.1 times. The thermal enhancement factor of the inserted tube under similar pumping power is evaluated and found to be above unity except for the single and the double co-twisted tapes. The quadruple counter-twisted tape insert provides the maximum thermal performance.
Keywords: Friction factor; Nusselt number; Thermal performance; Turbulator; Twisted tape arrangement